Interfacial characteristics of BIOfactor MTA and Biodentine with dentin. Issue 2 (29th November 2022) - Akbulut, Makbule Bilge; Mutlu, Şeref Nur; Soylu, Mehmet Ali; Şimşek, Emine
Abstract: The objective of this study was to characterize the interface between dentin and MTA‐Angelus (Angelus, Londrina, Brasil), Biodentine (Septodont, France) and BIOfactor MTA (Imicryl, Konya, Turkey) using scanning electron microscopy (SEM), energy disperse X‐ray spectroscopy (SEM‐EDS) and confocal laser scanning microscopy (CLSM). Fifteen dentin segments were obtained from previously extracted single‐rooted human teeth. Canal lumens were instrumented with diamond burs and then randomly filled with MTA‐Angelus, Biodentine or BIOfactor MTA and placed in distilled water or Hanks' Balanced Salt Solution (HBSS) for 28‐days. The samples were examined with SEM and the thickness of the interfacial layer measured. SEM‐EDS analysis was performed to determine principal elemental composition of the material, dentin, and interfacial area. The marginal adaptation of cements to dentin was assessed by confocal microscopy and the percentage of material penetration was calculated. An interfacial layer was evident in approximately 70% of SEM images in both MTA‐Angelus and BIOfactor samples. The thickness of interfacial layer was significantly higher in HBSS than in distilled water for all groups. MTA Angelus resulted in the thickest interfacial layer in distilled water while Biodentine had the thickest interfacial layer in HBSS. Calcium levels within the BIOfactor MTA–dentin interface were higher than both dentin and cement. Dentin penetration was higher in BIOfactor MTA and silicon was evident in all material‐dentin interfaces. All calcium silicate‐based materials promoted the formation of an interfacial layer. BIOfactor MTA exhibited promising characteristics with its good marginal adaptation even though it presented a moderately thick interfacial layer. Research Highlights: A distinguishable interfacial layer was observed in most of the samples within the BIOfactor MTA, MTA‐Angelus and Biodentine groups. The elemental constitution of the interfacial layer was different from that of the calcium silicate based materials. Abstract : Schematic illustration of experimental design.